2018
DOI: 10.3847/1538-4365/aac01d
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of the High-mass Protostellar Molecular Clump IRAS 16562–3959

Abstract: We present molecular line observations of the high-mass molecular clump IRAS 16562−3959 taken at 3 mm using the Atacama Large Millimeter/submillimeter Array (ALMA) at 1. 7 angular resolution (0.014 pc spatial resolution). This clump hosts the actively accreting high-mass young stellar object (HMYSO) G345.4938+01.4677, associated with a hypercompact Hii region. We identify and analyze emission lines from 22 molecular species (encompassing 34 isomers) and classify them into two groups, depending on their spatial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 125 publications
4
32
0
Order By: Relevance
“…Specially, the interstellar medium (ISM) is known for its chemical lavishness, with radiofrequency line detections of more than 200 species including small hydrocarbons, molecular radicals, and a plethora of complex organic molecules (COMs) to date [10][11][12][13][14][15][16][17]. The analysis of rotational spectra also allows the investigation of the morphology and evolutionary stage of a particular environment or body [18][19][20], as well as the determination of its physical properties [21,22]. Recent technological advances on single dish and interferometry radio antennas have resulted in facilities with remarkable sensitivity and resolution (e.g., the Atacama Large Millimeter Array), consequently increasing the demand for more precise rotational spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, the interstellar medium (ISM) is known for its chemical lavishness, with radiofrequency line detections of more than 200 species including small hydrocarbons, molecular radicals, and a plethora of complex organic molecules (COMs) to date [10][11][12][13][14][15][16][17]. The analysis of rotational spectra also allows the investigation of the morphology and evolutionary stage of a particular environment or body [18][19][20], as well as the determination of its physical properties [21,22]. Recent technological advances on single dish and interferometry radio antennas have resulted in facilities with remarkable sensitivity and resolution (e.g., the Atacama Large Millimeter Array), consequently increasing the demand for more precise rotational spectroscopic data.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest in structure is methanol (CH 3 OH), which is frequently detected in the ISM (e.g. Leurini et al 2016;Guzmán et al 2018;Chacón-Tanarro et al 2019). Its formation occurs on dust grain surfaces at dust temperatures of ∼12 K by subsequent hydrogenation of CO, which has been quantified by theoretical studies and in the laboratory (e.g.…”
mentioning
confidence: 99%
“…as well as its morphology and evolutionary stage (e.g., Wyrowski et al 1999;Beuther et al 2005;Guzmán et al 2018). In this context, experimental and theoretical rotational spectroscopy share a symbiotic relationship that is fundamental to broaden our percipience of the physics and chemistry of the ISM (see, e.g., Puzzarini 2017; Puzzarini and Barone 2020; Cerqueira et al 2020;Santos et al 2020).…”
Section: Rotational Transitionsmentioning
confidence: 99%
“…Later, Lovas clouds. Since its first detection, CH 3 CCH has been extensively studied toward star-forming regions (e.g., Zhang et al 2014;Taniguchi et al 2018;Guzmán et al 2018;Bøgelund et al 2019;Calcutt et al 2019), and has proven to be a reliable tracer of their physical conditions (e.g., Bergin et al 1994). It has also been observed toward extagalactic sources, such as M 82, NGC 253, and NGC 1068 (Mauersberger et al, 1991;Qiu et al, 2020), and even toward a planetary nebula, as recently reported by Schmidt and Ziurys (2019).…”
Section: The Spectral Tracer Methyl Acetylenementioning
confidence: 99%
See 1 more Smart Citation